Restorative Justice in the Asia Pacific Region: Acting Fairly, Being Just - Goulding, Dot; Steels, Brian (Springer NY, 2012)
In this paper the authors explore a variety of local and community restorative justice alternatives to retributive justice, including within an Asian context. Restorative justice is practiced in many forms throughout the region, from youth offending teams, juvenile justice panels, adult diversionary panels, through to family and community group conferences, healing and sentencing circles, restorative prisons and international truth and reconciliation councils. Restorative justice processes are applied throughout Europe, Asia and the Americas both within and outside of criminal justice jurisdictions where people desire effective and therapeutic interventions and where one party is able to provide a guilty or “not denied” plea and where victims of crime take the opportunity to participate.